Comparison of Forsythia suspensa leaf fermented tea in the four different regions of Shanxi Province: quality, functional ingredients, and bioactivity - Li, Lijuan; Zhao, Yating; Zhang, Shu; Zhang, Xiaohong; Duan, Guofeng (Frontiers in Sustainable Food Systems, 2024)
Background: Forsythia suspensa (F. suspensa) is a plant of the Oleaceae family that is used as a medicinal plant. It is a traditional Chinese medicine that functions in clearing heat and detoxification.F. suspensa contains various phytochemicals, such as lignans, flavonoids, triterpenoids, and phenylethanolic glycosides; however, the main active phytochemical in F. suspensa is phillygenin, which has lipid-lowering, antioxidant, antihypertensive, and tyrosinase inhibitory effects. However, the content of phillygenin in F. suspensa is very low, limiting its application.Methods: This study used wild F. suspensa leaves (FSL) from Lingchuan County (LC), Anze County (AC), Pingshun County (PS), and Pingding County (PD) in Shanxi Province as experimental materials. Through a single factor and orthogonal experimental design, the fermentation time, temperature, and humidity of F. suspensa leaf fermented tea (FSLFT) were optimized using a black tea fermentation machine.